Pengaruh Penerapan Sistem Informasi Akuntansi, Budaya Organisasi, Motivasi Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan - Triwinasis, Triwinasis; Hastuti, Sri; Widiastuti, Sri Wahyuni (Jurnal Bisnis dan Kewirausahaan, 2023)
This study aims to partially determine the variables of the application of accounting information systems, organizational culture, work motivation, and work discipline on employee performance at BPPKAD Cilacap Regency and to determine the variables that have a dominant influence on employee performance. This research is a descriptive study and the data used in this study are primary, namely by distributing questionnaires directly to 79 employees at BPPKAD Cilacap Regency. The sampling technique in this study used a purposive sampling technique and obtained 59 samples. Data analysis used descriptive statistical tests, data quality tests, and multiple linear regression analysis. The hypothesis was tested using a t-test with SPSS for windows version 26.0. The results of this study indicate that the application of accounting information systems, organizational culture, work motivation, and work discipline positively affect employee performance. It is concluded that the research results on employee performance imply that it can improve the performance of its employees, because by having high performance, in carrying out their duties and responsibilities employees can create loyalty and work spirit so that goals can be achieved optimally and result in increased BPPKAD services in Cilacap Regency to the public.